Acrokeratosis Paraneoplastica Associated with Cervical Squamous Cell Carcinoma. (22nd December 2016) - Squires, Bryan; Daveluy, Steven D.; Joiner, Michael C.; Hurst, Newton; Bishop, Michael; Miller, Steven R.
Abstract : Background . Acrokeratosis paraneoplastica, or Bazex syndrome, is a paraneoplastic syndrome characterized by cutaneous psoriasiform lesions with associated acral erythema and scale, as well as nail changes, including onycholysis and ungual dystrophy. Its most advanced, severe form involves the trunk, elbows, and knees. It is typically associated with upper aerodigestive tract malignancies in males. Rare cases associated with gynecological cancers have been reported, including uterine adenocarcinoma, as well as ovarian and vulvar squamous cell carcinomas. Cutaneous manifestations often precede cancer diagnosis. In most reported cases, skin changes resolve when the underlying malignancy is adequately treated. Main Observations . We present the case of a 56-year-old female diagnosed with acrokeratosis paraneoplastica following the discovery of FIGO stage IIB cervical squamous cell carcinoma (SCC). Scaling, hyperpigmentation, xerosis, and fissuring were noted on the patient's hands, feet, legs, arms, and lower back. Pitting was noted on her fingernails. Her cervical cancer was successfully treated with chemoradiotherapy, after which her cutaneous lesions persisted for two months before resolving. Conclusions . The presentation of acrokeratosis paraneoplastica in this context is atypical. Reports of associations with gynecological cancers, as in our patient's case, are exceedingly rare.